1984
DOI: 10.1002/jctb.280340104
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐transfer coupling in microbial fuel cells. 2. performance of fuel cells containing selected microorganism—mediator—substrate combinations

Abstract: Various phenoxazine, phenothiazine, phenazine, indophenol and bipyridilium derivatives were tested for their effectiveness as redox mediators in microbial fuel cells containing Alcaligenes eutrophus, Bacillus subtilis, Escherichia coli, or Proteus vulgaris as the active biological agent, and glucose or succinate as the oxidisable substrate. A ferricyanide-Pt cathode was used. The open-circuit cell e.m.f.'s increased in the order of increasing negative formal redox potentials at pH 7(Ez) of the redox compounds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(79 citation statements)
references
References 10 publications
4
71
0
4
Order By: Relevance
“…This modelling study is based on the detailed experimental observations by Bennetto's group in the 1980s [5,21,24] and Kim's work in the late 1990s [11]. For convenience, their experimental setup is briefly described here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This modelling study is based on the detailed experimental observations by Bennetto's group in the 1980s [5,21,24] and Kim's work in the late 1990s [11]. For convenience, their experimental setup is briefly described here.…”
Section: Methodsmentioning
confidence: 99%
“…Batch operation of the MFC is simulated (experiments by Kim et al [11], Thurston et al [24]. Alternatively, repeated substrate addition in a fed-batch mode is also considered (experiments by [5]. Soluble components diffuse between the bulk liquid and the electrode through a mass transfer boundary layer (MTBL) of thickness, L L , adjacent to the anode.…”
Section: Computational Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most MFCs are structurally similar to other fuel cells; they are electrochemically inactive and require mediators to facilitate the transfer of electrons (Delaney 1984). Utilization of microbes which are electrochemically active was a major step in the manufacture and advancement of microbial fuel cell reactors (Kim et al 1999a, b).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Previous research efforts have focused on maximising current output by utilising soluble electron mediators which allow for electron transfer from the enzymatic active sites within the cells to the electrodes. [5][6][7][8][9] Nevertheless, the use of soluble mediators requires continuous replenishment, which makes their use unsustainable, costly and in some cases even harmful to the environment. 7,10 Recent investigations in the field of bioelectronics have demonstrated that electron shuttling via immobilized redox mediators such as polymeric osmium complexes 11,12 and polymeric azines [13][14][15] (e.g.…”
mentioning
confidence: 99%